Social Financial Inclusion of Digital Based and Cooperation to Increase Competitiveness in Baitul Maal Wat Tamwil - Fatkhur Rohman Albanjari (Sekolah Tinggi Agama Islam Taruna Surabaya, 2023)
This research is aimed to find out the Social Financial Inclusion of Digital-based and Cooperation in Baitul Maal Wat Tamwil (multisite study of BMT UGT Nusantara Pasuruan and BMT NU Ngasem Bojonegoro). This research used descriptive qualitative method. Data analysis used in this research was done by collecting data sources through profound interview, observation, and the Internet, social media of BMT UGT Nusantara Pasuruan and BMT NU Ngasem Bojonegoro. The technic of analyzing qualitative data in this research was done gradually through data colleting, data reduction, data display, and conclusion. The finding showed that digital implementation of both BMT is done by using social media and promotion, submission and responsibility for social financial management. The cooperation program was also done by both BMT in order that the social financial can be inclusive. The cooperation concepts that was done by both BMT were; cooperation with inter-BMT sector, cooperation with off-BMT institutions, and cooperation with local organizations or communities. The result showed that the inclusion of digital-based social financial and cooperation in this research is able to increase the competitiveness of BMT.